Product Design Innovation and Branding in the Development of Risoles MSMEs: Inovasi Desain Produk dan Branding dalam Pengembangan UMKM Risoles - Yulianto, Fendy; Arbansyah; Ilham, Muhammad Fauzan Nur; Atiqah, Nur Quratul Nabila; Nurdin, Andi; Bakri, Umar (Wadah Inovasi Indonesia, 2024)
Youth misbehavior, especially among Generation Z, has become an increasing social problem in the digital era. This community service aims to identify the factors that cause juvenile delinquency and assess the effectiveness of legal socialization in increasing students' legal awareness at MTs Al-Hidayah Samboja, Tanjung Harapan Village. Activities were carried out using observation and legal socialization methods, which included material presentation and interactive discussions with class IX students. The results showed that psychological, social, and subcultural factors play an important role in influencing adolescent deviant behavior. Legal socialization proved effective in improving students' understanding of the legal consequences of deviant actions and the importance of complying with social norms. In conclusion, an interactive legal education approach can increase legal awareness and help reduce the potential for juvenile delinquency, especially if supported by a conducive social environment.